Making Intergenerational Otherwise: Kids Enacting Decolonial, Queer, Crip Futures - Chazan, May; Hill, Megan (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
In this paper, we reflect upon the lessons learned in an intergenerational arts-based research workshop held in 2023 on Michi Saagiig Anishinaabe territory. The workshop brought together activists ages ten to one hundred, meaningfully including children and older adults as equal participants. Bridging writing on queer, crip, decolonial futures with scholarship on critical aging studies and childhood studies, we argue that radical intergenerationality is central to reworlding, or to imagining and making livable, liberatory futures. Centered around three vignettes from the workshop, this article explores how the presence of children and their intergenerational interactions offered teachings about accountability, joy, and honouring diverse body-minds. We conclude that, in a process of radical imagination, the youth offered us a glimpse of the intergenerational, decolonial, queer, crip futures we dream of and helped to create them in the space we shared.